Knowledge, Attitude And Practice Regarding Nickel Hypersensitivity In Patients Undergoing Orthodontic Therapy Among Interns. - A Questionnaire Survey. - A, SANDHYA.; VARGHESE, REMMIYA MARY; P, SENTHIL MURUGAN. (The journal of contemporary issues in business and government, 2021)
Nickel is one of the most common causes of allergic contact dermatitis and produces more allergic reactions than all other metals combined. Currently, several brands of orthodontic wires are made of nickel titanium alloy and potentially have a high enough nickel content to provoke manifestations of allergic reactions in the oral cavity. The main objective of this study is to evaluate the knowledge and awareness on nickel hypersensitivity in patients among interns in a private dental college. The study was conducted in a private dental college, Chennai. The study group consisted of the interns and postgraduate students. Total number of studies included in the study was 200.The statistical analysis was done using SPSS software (SPSS version 21.0, SPSS, Chicago II, USA). The data was analysed using a chi- square test. The p value of less than 0.05 was considered to be statistically significant.About 73% of them are aware about Nickel Hypersensitivity and 74.5% are aware that Nickel hypersensitivity is one of the most common causes for allergic contact dermatitis. Higher number of females reported to know about Nickel Hypersensitivity when compared to males. There was no significant difference between the gender and awareness about Nickel Hypersensitivity.Chi- square value: 0.059, p value: 0.807. Dental students in this study have a good level of knowledge and positive attitude towards nickel hypersensitivity in patients. However, the knowledge acquired must be implemented in their daily practice and provide the better treatment required for the patients. A better knowledge of nickel hypersensitivity is essential for safe practice in dentistry. This will ensure the provision of better and safer dental health care services for the population.